Glycine Transporters and Its Coupling with NMDA Receptors - Zafra, Francisco; Ibáñez, Ignacio; Bartolomé Martín, David; Piniella, Dolores; Arribas-Blázquez, Marina; Giménez, Cecilio (My University, 2017)
Glycine plays two roles in neurotransmission. In caudal areas like the spinal cord and the brainstem, it acts as an inhibitory neurotransmitter, but in all regions of the CNS, it also works as a co-agonist with L-glutamate at N-methyl-D-aspartate receptors (NMDARs). The glycine fluxes in the CNS are regulated by two specific transporters for glycine, GlyT1 and GlyT2, perhaps with the cooperation of diverse neutral amino acid transporters like Asc-1 or SNAT5/SN2. While GlyT2 and Asc-1 are neuronal proteins, GlyT1 and SNAT5 are mainly astrocytic, although neuronal forms of GlyT1 also exist. GlyT1 has attracted considerable interest from the medical community and the pharmaceutical industry since compelling evidence indicates a clear association with the functioning of NMDARs, whose activity is decreased in various psychiatric illnesses. By controlling extracellular glycine, transporter inhibitors might potentiate the activity of NMDARs without activating excitotoxic processes. Physiologically, GlyT1 is a central actor in the cross talk between glutamatergic, glycinergic, dopaminergic, and probably other neurotransmitter systems. Many of these relationships begin to be unraveled by studies performed in recent years using genetic and pharmacological models. These studies are also clarifying the interactions between glycine, glycine transporters, and other co-agonists of the glycine site of NMDARs like D-serine. These findings are also relevant to understand the pathophysiology of devastating diseases like schizophrenia, depression, anxiety, epilepsy, stroke, and chronic pain. Keywords: Astrocytes; Glutamate; GlyT1; Glycine; NMDA receptors; Schizophrenia; Transport.